Integrative resilience in action: Stories from the frontlines of climate change and the Covid-19 pandemic - Camponeschi, Chiara (Frontiers in Sustainable Cities, 2022)
Interest in resilience and vulnerability has grown remarkably over the last decade, yet discussions about the two continue to be fragmented and increasingly ill-equipped to respond to the complex challenges that systemic crises such as climate change and the Covid-19 pandemic pose to people, places, and the planet. Institutional interventions continue to lag behind, remaining predominantly focused on technocratic framings of vulnerability and resilience that do not lead to a more robust engagement with the reality of the changes that are underway (Camponeschi, 2021). This paper provides a blueprint for facilitating intersectional resilience outcomes that ensure that as a society we are not merely surviving a crisis, but are committing to interventions that place equity, solidarity, and care at the center of healthy adaptation and wellbeing. First, it traces the evolution of resilience from a strictly ecological concept to its uptake as a socio-ecological framework for urban resilience planning. Next, it argues that current framings of vulnerability should be expanded to inform interventions that are locally relevant, responsive, and ‘bioecological’. The integrative resilience model (Camponeschi, 2022) is then introduced in the second half of the paper to challenge the scope of formal resilience plans while providing an entry point for renewed forms of resistance and recovery in the age of neoliberalism-fueled systemic crisis. The three pillars of the model are discussed alongside a selection of scalable and adaptable community-driven projects that bring this approach to life on the ground. By being rooted in lived experience, these innovative initiatives amplify and advance the work of frontline communities who are challenging and resisting the neoliberalization not only of urban governance and resilience, but of wellbeing and (self-) care more broadly.